Generation of (34)S-substituted protein-bound [4Fe-4S] clusters using (34)S-L-cysteine - Crack, Jason C (Biol Methods Protoc, 2019)
The ability to specifically label the sulphide ions of protein-bound iron–sulphur (FeS) clusters with (34)S isotope greatly facilitates structure–function studies. In particular, it provides insight when using either spectroscopic techniques that probe cluster-associated vibrations, or non-denaturing mass spectrometry, where the ∼+2 Da average increase per sulphide enables unambiguous assignment of the FeS cluster and, where relevant, its conversion/degradation products. Here, we employ a thermostable homologue of the O-acetyl-l-serine sulfhydrylase CysK to generate (34)S-substituted l-cysteine and subsequently use it as a substrate for the l-cysteine desulfurase NifS to gradually supply (34)S(2−) for in vitro FeS cluster assembly in an otherwise standard cluster reconstitution protocol.